COVID-19 susceptibility and vaccination coverage for measles, rubella and mumps in students and healthcare workers in Trieste hospitals (NE Italy). (April 2022) - Cattaruzza, Eleonora; Radillo, Lucia; Ronchese, Federico; Negro, Corrado; Rui, Francesca; De Michieli, Paola; Larese Filon, Francesca
Abstract: Background: Measles, mumps, and rubella (MMR) vaccines have been suggested as preventive measures to protect subjects from the worst sequelae of COVID-19 infection because neutralizing antibodies can cross-react with other viruses. Aim: To verify COVID-19 infection in MMR vaccinated and non-vaccinated healthcare workers and medical students in Trieste Hospitals. Results: Nurse aids resulted in significantly more infections than structured physicians (OR 1.80; 95% CI 1.14–2.80) while students resulted in less infections (OR, 0.66; 95% CI 0.43–1.01). The presence of an MMR vaccination was inversely associated with COVID-19 (OR, 0.77; 95% CI 0.61–0.96) but only in univariate analysis. In the multivariable logistic regression analysis, MMR vaccination lost statistical significance (OR, 0.86; 95%CI 0.62–1.20). On 13 HCWs hospitalized for COVID-19, 11 resulted not vaccinated for MMR. Discussion: Our study found a mild, non-significant reduction in SARS-CoV-2 infections in workers vaccinated with MMR.